THE POWER GAME IN SPECIAL EDUCATIONAL POLICIES IN RECENT DECADES - Jacaúna Neto, Antonio Francisco; Patriarca, Amanda; Lima, Cícero Batista dos Santos; Machado, Cleide Pires; de Sousa, Giselle Alves Dias; Machado, Luiza Helena Barreira (Seven Editora, 2025)
The publication of numerous Brazilian government legislation in recent decades regarding inclusion highlights the persistent political and epistemological dispute surrounding special education in Brazil, as well as the materialization of these convictions in the training of teachers and professionals in special education. This article reviews legislative discourses from recent decades, aiming to clarify the political game in which special education finds itself. Using Foucauldian Discourse Analysis and the influences of Ball's Policy Cycle as methodology, we compare the various pieces of legislation, especially the two most recent decrees in this area (Decrees 10,502 of 2020 and 12,686 of 2025), which address the topic and its variants, such as the training of professionals working in the field. The resulting findings highlight many limitations and some advances in this political game, which should be aimed at promoting the inclusion of people with disabilities.DOI: https://doi.org/10.56238/sevened2025.038-034